The private residential market in Singapore - Chua, Poh Chin (2014)
In this project, we study the private residential market trend for the past 14 years and the factors affecting the trend. Some of the factors are demographics, demand from HDB upgraders, foreign buyers and expatriates, economic growth and supply.